2006
DOI: 10.1111/j.1744-9987.2006.00358.x
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Liver Support System in China: A Review Over the Last 30 Years

Abstract: Severe viral hepatitis with high mortality is the most common cause of liver failure in China. Treatment of severe viral hepatitis by hemoperfusion was initially adopted in the late 1970s and early 1980s. Following 10 years of development in China, a plasma exchange (PE)-centered artificial liver support system (ALSS), principally dependent on PE technology was developed. Based on the condition and symptoms of each patient, PE was given alone, or combined with hemodialysis, hemofiltration, hemodiafiltration, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 15 publications
1
50
0
Order By: Relevance
“…Our previous study has demonstrated that ALSS can efficiently decrease the mortality of patients with severe hepatitis of early and middle stages [3]. However, for patients with ACLF, since hepatocytes undergo massive denaturation, necrosis and dysfunction, it is difficult to completely reverse the clinical course of the disease with routine medical management and even combined with ALSS.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study has demonstrated that ALSS can efficiently decrease the mortality of patients with severe hepatitis of early and middle stages [3]. However, for patients with ACLF, since hepatocytes undergo massive denaturation, necrosis and dysfunction, it is difficult to completely reverse the clinical course of the disease with routine medical management and even combined with ALSS.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial liver support system (ALSS) has been proved to be an effective way to improve liver function and thus serve as a bridge to LT [10]. After such treatment, total bilirubin, international normalized ratio, encephalopathy, and serum creatinine can be remarkably improved and thus MELD score was reduced [11].…”
Section: Introductionmentioning
confidence: 99%
“…A significant improvement was observed in the World J Emerg Med, Vol 5, No 3, 2014 survival rate compared to another study. [7] In our study, the survival rate of patients with nonvirus-caused liver failure was 70%, but the survival rate of patients with virus-caused liver failure was 36.4%. The finding suggested that the combined use of nonbiological artificial liver technology plays a significant role in improving the clinical outcomes.…”
Section: Discussionmentioning
confidence: 93%
“…The survival rate was 42.5% for MODS patients with ALF after treatment with plasma exchange and CVVHDF. [7] In our study, the liver function score was≥IV according to MODS score, and PTA was less than 30%. All patients were in the stage of advanced liver failure according to liver failure treatment guidelines.…”
Section: Discussionmentioning
confidence: 99%